Media Pengembangan Pemahaman Hadis Nabi - Taqiuddin Zarkasi (Al-Riwayah : Jurnal Kependidikan, 2016)
Hadist understanding is generally divided into two, namely, textual and contextual understanding. Asbabal wurud concept has close links with other concepts that are also very important, nasikh mansukh, related with religious teachings, both the Qur’an and al-Sunnah. In the concept of asbab al-nuzul, asbab al-wurud and nasikh mansukh contained their historical consciousness among Islamic jurists. This historical consciousness becomes one of the cornerstones of hope that Islam will be better in responding the challenges of the times in the future. The typology of scholars and Muslim understanding of the hadist is classified into two parts. First is the typology of understanding who believes that hadist as a source of the teachings of Islam, regardless of the historical process of collecting hadist and orthodox teachings formation process. Second is people who believe in tradition as a source of both the teachings of the religion of Islam, but with a critical outlook and consider the historical origins (asbabal-wurud) of hadist. This article describes the position of asbabul wurud contextually.